1998
DOI: 10.4131/jshpreview.7.1225
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Diffusion and Trans-cis Isomerization of Substituted Diphenyl Polyenes in the Compressible Region of Supercritical Fluids.

Abstract: We examine rotational diffusion and trans-cis isomerization of two Biphenyl polyenes, diphenylbutadiene (DPB) and hydroxymethyl-stilbene (HMS) in supercritical fluid CO2 and ethane. The results of density dependent rotational diffusion measurements are interpreted using a model which we have recently developed for rotational diffusion in compressible fluids. Comparison of DPB and HMS fluorescence lifetimes indicate that the rate of the isomerization reaction of DPB is nearly independent of density while HMS ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
5
10
0
Order By: Relevance
“…A comparison of HMS and DPB in supercritical CO 2 demonstrates the influence of a polar functional group on solvent−solute friction. A comparison of HMS in supercritical ethane and CO 2 (Figure ) emphasizes the specificity of the polar solute interaction with CO 2 . Interestingly, the HMS−ethane results exhibit the same modest increase with increasing density that we have observed in the DPB−CO 2 system.…”
Section: Rotational Diffusion In Scfs and Polar Liquidssupporting
confidence: 70%
“…A comparison of HMS and DPB in supercritical CO 2 demonstrates the influence of a polar functional group on solvent−solute friction. A comparison of HMS in supercritical ethane and CO 2 (Figure ) emphasizes the specificity of the polar solute interaction with CO 2 . Interestingly, the HMS−ethane results exhibit the same modest increase with increasing density that we have observed in the DPB−CO 2 system.…”
Section: Rotational Diffusion In Scfs and Polar Liquidssupporting
confidence: 70%
“…First, the free rotor times used in their analysis are seen to substantially overestimate the true free rotor times of these solutes. As noted by Anderton and Kauffman, , within their modeling scheme, changes in these times have a dramatic impact on the extent of density augmentation deduced from rotation times. If the values of the free rotor times determined here (2.1 ps for DPB and 1.9 ps for HMS) were employed, significant and comparable density augmentation in the DPB/CO 2 and HMS/CO 2 systems would be implied by their analysis.…”
Section: Resultsmentioning
confidence: 94%
“…They concluded that the local density in the vicinity of DPB differs little from that of the bulk fluid, whereas the local solvent density around HMS is ∼40% greater than the bulk solvent density. By analogy to the pronounced differences in rotational times observed for HMS in liquid alkane versus alcohol solvents, Kauffmann and co-workers attributed this difference in augmentation to the ability of HMS to hydrogen bond to CO 2 . ,, …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations